The role of the midwife in the care of a neonate with cleft palate and vascular ring – case report - Szczypta, Karolina; Ostrogórska-Gonszewska, Patrycja; Mierzwa, Anna (Nursing Problems / Problemy Pielęgniarstwa, 2021)
Cleft lip and/or palate is the most common craniofacial malformation. Aside from the visual facial defect, it results in numerous difficulties associated with sucking, swallowing, and breathing, as well as with speech and hearing. A variety of heart and vascular defects makes them the most common congenital anomalies. Vascular ring is an anomaly involving abnormal development of large heart vessels. Aim of the study was to present nursing care of a neonate born with a cleft hard palate and bilateral cleft lip, as well as with a vascular ring. An individual case method was used to prepare the study. To characterise the study neonate, the following research methods were used: observation, measurement of basic parameters, and analysis of the patient’s medical records. The study describes a male neonate born to G1P1 by natural delivery at 40 weeks of gestation, who immediately after birth was admitted to the department of neonatal pathology due to a craniofacial cleft and prenatally diagnosed heart defect. The major nursing problems occurring in the child were associated with the craniofacial cleft, resulting in feeding difficulties. Moreover, the malformations diagnosed created a risk of general disorders and required increased observation and provision of emotional support. The role of a midwife taking care of a neonate with craniofacial cleft and heart defect is primarily careful monitoring of the patient, nursing, and educating the parents to prepare them for the care of the child after completion of hospitalisation.